It Takes a Village: A Multi-Institution, Multi-Role Panel on Contract Cheating - Grue, Dustin; Boisvert, Sheryl; Eaton, Sarah Elaine; Ferguson, Corrine; Moya, Beatriz Antonieta; Radke, Susan; Seeland, Josh; Wheatley, Bronwen (Canadian Perspectives on Academic Integrity, 2023)
Members of the Alberta Council on Academic Integrity (ACAI) Contract Cheating Working Group will discuss how the collective, multi-institutional nature of their work has helped to provide practical interventions for contract cheating (Clarke & Lancaster, 2006), addressing in particular this mode of misconduct's multilateral and predatory nature. Student academic misconduct in post-secondary education and research has predominantly been understood to be perpetrated by individuals undertaking unilateral action (Eaton et al., 2019). We can observe this, for example, in how motives for academic misconduct tend to be studied in psychological, sociological, or criminological terms (e.g. Rundle et al., 2019) while the ‘supply side’ (Medway et al., 2018) and structured nature (Grue et al., 2021) of contract cheating requires more exploration. Contract cheating undermines the expectation of unilateral action by virtue of its multilateral (i.e. contractual) nature, involving networks of suppliers and consumers, thereby complicating the relationship between the perpetrator and the act of misconduct and frustrating efforts to make meaningful interventions. Addressing contract cheating takes a village. Through the lens of diversified roles and from the perspectives of multiple post-secondary institutions, panel members will discuss how to engage contract cheating collectively, provide specific and concrete projects they have collaboratively undertaken to address contract cheating issues – including videos and other digital resources – and discuss recent, instructive contract cheating cases. Participants will have access to situated insights, experiences, and resources to take away and use as-is or adapt to their own needs.